2018
DOI: 10.1002/fam.2643
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rheological model for creep strain evolution in steel and aluminium at high temperature

Abstract: Summary The paper presents a rheological model capable of reproducing the temperature‐, stress‐, and time‐dependent strain component, which occurs in steel and aluminium during exposure to high temperature. The model is capable of providing the creep strain output for the primary, secondary, and tertiary creep phases for both steel and aluminium. Constitutive parameters of the rheological model are calibrated using 2 recent coupon test studies based on the European steel grade S275JR and aluminium grade EN6082… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Torić et. al [13] adapted the aforementioned model to represent the creep behaviour of steel and aluminium at constant high-temperature. Furthermore, Torić and Burgess [14] developed a unified rheological model for the analysis of strain development in steel at high-temperature in the case of transient heating.…”
Section: Overview Of Creep Modelsmentioning
confidence: 99%
“…Torić et. al [13] adapted the aforementioned model to represent the creep behaviour of steel and aluminium at constant high-temperature. Furthermore, Torić and Burgess [14] developed a unified rheological model for the analysis of strain development in steel at high-temperature in the case of transient heating.…”
Section: Overview Of Creep Modelsmentioning
confidence: 99%
“…Unrecoverable plastic deformation generated due to the thermal creep during the heating process, which could affect the mechanical properties reduction factors of Galfan-coated steel cables after experiencing elevated temperature. 18,19 In order to considering the influence of the thermo- After that, a constant tensile load increment of 10 MPa/s, as per the GB/T 31314-2014, 20 was applied until failure at ambient Table 2.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…However, the components in the actual structure are generally under stress state when a fire occurs. Unrecoverable plastic deformation generated due to the thermal creep during the heating process, which could affect the mechanical properties reduction factors of Galfan‐coated steel cables after experiencing elevated temperature 18,19 . In order to considering the influence of the thermo‐mechanical coupling effect in the fire on the postfire mechanical properties of the Galfan‐coated steel cables, the transient‐state test method is adopted in this paper.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…A special problem in civil engineering practice is the behaviour of aluminium when subjected to elevated temperatures (fire). Considering the topicality of worldwide research focusing on the behaviour of aluminium in fire [5][6][7], the studies on behaviour of aluminium alloys and structural elements in fire conditions have also been a subject of research in the Republic of Croatia [8][9][10]. Aluminium structures are sensitive to the effects of high temperature due to the high value of the thermal conductivity coefficient (>100 W/m 2 K) and the low melting point of the material (between 560-660 °C) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…High value of thermal conductivity causes faster heating of aluminium compared to steel, while low melting temperature increases creep sensitivity of aluminium, which was the initial motivation for the research started in the Republic of Croatia. Current research in the field of aluminium behaviour in the field of fire in the Republic of Croatia is related to the analysis of time-dependent deformation (creep) that occurs in the presence of certain thermo-mechanical boundary conditions, all of which have been presented in a series of scientific papers [8][9][10]. The aforementioned studies demonstrated the creep sensitivity of aluminium columns and quantified their creep resistance expressed as the total time during which aluminium columns retain their load-bearing capacity for a given temperature and load utilization factor.…”
Section: Introductionmentioning
confidence: 99%